Assessment of factors influencing the export of coconut products from the Philippines : Johansen Cointegration Analysis - Moreno, Marife Luardo; Kuwornu, John K. M.; Datta, Avishek; Loc, Thai Nguyen; Asian Development Bank {u2013} Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
The Philippines is the second largest producer of coconut in the world. Majority of the land in the Philippines is cultivated for agricultural purposes. Coconut industry is considered as the lifeblood of Philippine agriculture acclaimed as the country{u2019}s major pillar in foreign exchange revenue. The top agricultural export commodities as of 2016 are coconut oil (22%), fresh banana (14%), pineapple products (14%), and tuna (5%). Coconut steadily contributed 4% of the total gross value added from the crop subsector. The production of coconut in the country showed a declining trend that influences the export sector. In a trade of raw coconut, Philippines ranked in the 7th exporter in the world. The country is the number one exporter of coconut oil and copra cake in the world statistics from the Food and Agriculture Organization (2018). This study aims to investigate the relationship between export quantity and value of raw coconut, coconut oil, and copra cake and the macroeconomic factors such as gross domestic product, population, exchange rate and quantity of production over the period from 1961 to 2017 in the theory of gravity model in international trade. The variables are stationary at level and integrated at the first and second difference. The optimal lag of the raw coconut export quantity and value is two. The optimal lag of three is the result of the coconut oil export value, copra cake export quantity and copra cake export value. Co-integration existed between the explanatory variables and independent variables by eleven to twelve co integrating vectors according to Johansen co-integration test. The co-integration indicates that the model develops a long-run relationship allowing the estimation of vector error correction model to assess the factors influencing export of raw coconut, coconut oil, and copra cake from the Philippines to the three importing countries per coconut product. In this estimation model, the short-run and long-run dynamics of the variables were identified. The error correction term represents the speed of adjustment that the dependent variable returns to its equilibrium level in case of a shock after the gradual correction of the explanatory variables. The results revealed that the factors influencing the export of raw coconut in the short-run are the one year lag of the export quantity of raw coconut negatively influenced the export quantity of raw coconut. Also, the one year lag of the export value of raw coconut negatively influenced the export value of raw coconut. In the long-run, the factors that positively influenced the export quantity and value of raw coconut are the coconut production quantity from the Philippines, the gross domestic product of Hong Kong, the population of China, the population of Japan, the exchange rate of China and Japan. On the other hand, the factors that negatively influenced the export quantity and value of raw coconut are the gross domestic product of Japan, the population of the Philippines, the population of Hong Kong, and the exchange rate of Hong Kong. The results revealed that the factors influencing the export of coconut oil in the short-run are the one year lag of the export value of coconut oil negatively influenced the export value of coconut oil. The one year lag of the gross domestic product of the Philippines positively influenced the export value of coconut oil. Also, the one year lag of the population of the Netherlands positively influenced the export value of coconut oil. In the long-run, the factors that positively influenced the export value of coconut oil in the are the coconut production quantity from the Philippines, the gross domestic product of the Philippines, the gross domestic product of China, the population of the Philippines, the population of the Netherlands, the exchange rate of China. Alternatively, the factors that negatively influenced the export value of coconut oil, in the long-run, are the gross domestic product of the Netherlands, the population of China, the population of the United States of America, and the exchange rate of the Netherlands. The results revealed that the factors influencing the export of copra cake in the short-run are the one year lag of export quantity of copra cake negatively influenced the export quantity of copra cake. The one year lag of the coconut production quantity from the Philippines positively influenced the export quantity of copra cake. Moreover, the one year lag of the export value of copra cake negatively influenced the export value of copra cake. In the long run, the factors that positively influenced the export quantity and value of copra cake are the coconut quantity of production from the Philippines, the gross domestic product of South Korea, the gross domestic product of Vietnam, the gross domestic product of China, the population of South Korea, the population of Vietnam, and the exchange rate of China. Contrarily, the factors that negatively influenced the export quantity and value of copra cake are the gross domestic product of the Philippines, the population of the Philippines, the population of China, the exchange rate of South Korea and China. The study provides the recommendations for the policy-makers of the government of the Philippines vis-à-vis the coconut industry sector of the country. First, the strong implementation of strategic and comprehensive trading development program to promote economic growth through frictionless trading among countries. Second, the supply of coconut should be managed. Third, it is significant for the government to also take a look on the welfare of coconut farmer. This connotes on the retention and encouragement of the coconut farmer to jointly achieved the coconut industry development roadmap. In this case, it is a win-win situation for the farmer and for the country. Fourth, the training support for technology, the product diversification, and the research and development on value addition should be supported by the government and coconut farmer organizations to promote high value coconut products in the world market. The technological support will increase the production and enhance the quality of coconut product to be more competitive in the international market. Fifth, the government should support the market development services in investment, and the trade promotion both in domestic and foreign market. Additionally, the development plans can be entwined together with investment of public goods such as the infrastructures to facilitate the export-led growth aim of the country. This research provides the empirical contribution to the existing literature on international trade of coconut in the Philippines. Further avenues of research are to study the factors influencing exports using the panel data analysis, the study of competitors analysis, and the comprehensive study on the influence of exchange rate in the Philippines export both in the short run and long run dynamics. Time dimension is the element of business economics focused on this paper for managerial decision-making of the policy-makers in the Philippines classified into short-run and long-run dimensions. The results of this research primarily contribute to the inclusive growth of export of coconut industry in the Philippines.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management
Thesis (M. Am.) - Asian Institute of Technology, 2018
Keywords: Coconut industry -- Philippines; Coconut